Społeczno-demograficzne i kulturowe uwarunkowania kształtowania zakresu i jakości usług hotelarskich - Jaremen, Daria E. (Socio-demographic and cultural conditions for the development of hotel services quality, 2005)
Socio-demographic environment and closely connected with it cultural one play an important role in the system of conditions for the development of hotel services quality. The significance and role of the named above types of macro-environment in the process of creating services of the required quality result mainly from their direct influence on such attributes of demand for hotel services as: size and structure, types and nature of needs and preferences, as well as the inclination of quests for traveling and motives in taking it up. The objective of the presented article is to illustrate the selected social, cultural and demographic aspects of hotel services development, which at present and in the near future should focus hotel managers’ in Poland and abroad on their quality and management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1095, s. 182-192